THE BUREAUCRATIZATION OF FAITH: THE POLITICAL BACKDROP OF INDONESIA’S FIRST SHARIA-COMPLIANT ECONOMIC LEGISLATION - Ahmad Fathan Aniq; Umi Chaidaroh (Universitas Nurul Jadid, 2026)
This study examines the political backdrop of the rise of Sharia-compliant economic rules during the final decade of Indonesia’s New Order regime. Through a critical lens of political economy, this study aims at analyzing the political-historical landscape that facilitated the birth of the nation’s first Islamic banking. Using a qualitative approach, this study employs a historical perspective to investigate the convergence of state power and legislative policy during the late 1980s and early 1990s. The research results indicate that the enactment of the Law No 7 of 1992 on Banking, which becomes the foundation of Islamic finance, served primarily as a strategic tool of state diplomacy aimed at perpetuating the New Order’s hegemony. Drawing on Tarek Masoud’s political economy framework, this study argues that Suharto pivoted toward a Sharia-compliant economic system to secure a new foundation of legitimacy among the burgeoning educated Muslim middle class. This maneuver was a calculated response to mitigate declining support from secular military factions and to co-opt the moral reputational advantage of Islamic institutions